(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Indian society presents a very complex picture of women’s status. There are rhetorical and historical evidences of highly empowered womanhood with simultaneous pejorative evidences of commoditized womanhood. Indian society worships the woman, as goddess of power (Durga), wealth (Lakshmi) and learning(Sarasvati).At the same time institutionalization of prostitution from historical times of “Devdasi” poses a threat to the women image of goddess(Devi). Most of the Indian deities are females. The pre-aryan Dravidian civilization in Mohan-jo-Daro and Harappa reflected an exalted image of women, prominently represented by mother goddess -).